PHYSICAL PROPERTIES AND RED COLOR VALUE IN QUALITY TESTING MIXTURE OF RICE BRAN AND SAWDUST - J. W., TAMBUNAN; HERNAMAN, I.; AYUNINGSIH, B.; ROSANI, U. (Majalah Ilmiah Peternakan; Vol 28 No 1 (2025): Vol. 28 No. 1 (2025), 2025)
This study aims to determine the effect of the addition sawdust with rice bran on the physical properties and red color value. This research used a Completely Randomized Design (CRD) with 5 treatments and repeated 6 times. The levels of sawdust addition in the treatments were P0 = 0%, P1 = 10%, P2 = 20%, P3 = 30%, and P4 = 40%. The variables observed were particle specific gravity, bulk density, porosity, and red color value. The data were analyzed using analysis of variance (ANOVA) followed by Dunnet test with P0 as the control treatment, and correlation and regression tests. The results showed that the physical properties of rice bran were: particle specific gravity (g/mL) 1,343, 1,304, 1,259, 1,209, and 1,162 (r = 98.42%), bulk density (g/mL) 0.363, 0.358, 0.347, 0.334, and 0.323 (r = 97.45%), porosity (%) 26.868, 27.442, 27.543, 27.634, and 27.781 (r = 81.50%), red color values 156, 146, 134 ,128, and 120 (r = 94.47%). It can be concluded that the mixing of sawdust in rice bran has a significant effect (p<0,05) and has a negative impact on particle density, bulk density and red color value, as well as a positive impact on po- rosity.